Analisis Perkembangan Kemampuan Keuangan Daerah Dalam Mendukung Pelaksanaan Otonomi Daerah - Lamya Najmuddin; Khazinun Katsiran (Jurnal Teknik dan Teknologi Indonesia, 2023)
The SAW (Simple Additive Weighting) method begins with determining the criteria or assessment measures that form the basis for determining an alternative or choice between two possible candidates in the decision-making process, and on the weight value. Then the data that has been obtained will be processed using the SAW (Simple Additive Weighting) method. After that the results of the calculations are ranked with the aim of getting the highest alternative, so that the determiners of the selection of scholarship recipients get scholarship recipient recommendations from the ranking results. In determining the selection criteria for scholarship recipients, the types of scholarships have been defined, namely Supersemar scholarships, Underprivileged scholarships, and Poor Student scholarships. Alternatives are obtained from scholarship applicant data which will later be processed using the SAW (Simple Additive Weighting) method. The results of the selection process for scholarship recipients produce weight values, criteria, alternatives and ranking results as material for decision making.